2011
DOI: 10.4061/2011/956053
|View full text |Cite
|
Sign up to set email alerts
|

Thickness in Entorhinal and Subicular Cortex Predicts Episodic Memory Decline in Mild Cognitive Impairment

Abstract: Identifying subjects with mild cognitive impairment (MCI) most likely to decline in cognition over time is a major focus in Alzheimer's disease (AD) research. Neuroimaging biomarkers that predict decline would have great potential for increasing the efficacy of early intervention. In this study, we used high-resolution MRI, combined with a cortical unfolding technique to increase visibility of the convoluted medial temporal lobe (MTL), to assess whether gray matter thickness in subjects with MCI correlated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Since the end of the 20th century, evidence from studies of postmortem autopsies have revealed that the initial neuronal lesions of neurofibrillary tangles originate in specific layers of two multimodal areas of the cortex, the entorhinal cortex and the perirhinal cortex Braak, 1991, 1995;Van Hoesen and Solodkin, 1993;Braak et al, 1998), and that lesions then progress to other parts of the medial temporal lobe (Zhan et al, 2009). Pathological changes propagate in a network-dependent manner and follow a predictable sequence that is accompanied by neuronal loss and that leads to cerebral atrophy (Burggren et al, 2011). Kordower et al found that the loss of neurons in layer II of EC was observed in individuals with MCI before the onset of dementia (Kordower et al 2001;Xu et al, 2000;Pennanen et al, 2004) and that this process was largely correlated with their memory loss.…”
Section: Early Degeneration Of Ecmentioning
confidence: 97%
See 2 more Smart Citations
“…Since the end of the 20th century, evidence from studies of postmortem autopsies have revealed that the initial neuronal lesions of neurofibrillary tangles originate in specific layers of two multimodal areas of the cortex, the entorhinal cortex and the perirhinal cortex Braak, 1991, 1995;Van Hoesen and Solodkin, 1993;Braak et al, 1998), and that lesions then progress to other parts of the medial temporal lobe (Zhan et al, 2009). Pathological changes propagate in a network-dependent manner and follow a predictable sequence that is accompanied by neuronal loss and that leads to cerebral atrophy (Burggren et al, 2011). Kordower et al found that the loss of neurons in layer II of EC was observed in individuals with MCI before the onset of dementia (Kordower et al 2001;Xu et al, 2000;Pennanen et al, 2004) and that this process was largely correlated with their memory loss.…”
Section: Early Degeneration Of Ecmentioning
confidence: 97%
“…As a member of the limbic circuitry, EC plays an important role as an interface between the neocortex and the hippocampus (Braak and Braak, 1995). Burggren et al (2011) found that EC was highly involved in initial episodic encoding, which was found to be most susceptible to early AD-related pathological changes. The main characteristic of AD-related neurofibrillary changes are neurofibrillary tangles, neuropil threads, and argyrophilic components of neuritic plaques (Braak and Braak, 1995).…”
Section: Early Degeneration Of Ecmentioning
confidence: 98%
See 1 more Smart Citation
“…The ERC is recognized as an early-affected brain region in AD, and in a recent article its thinning was correlated with clinical features of the disease and predicted cognitive decline. ERC thickness reduction is associated with both longitudinal MMSE and ADAS-cog score changes (Velayudhan et al, 2013) and predicts episodic memory decline in MCI (Burggren et al, 2011). The analogy between AD patients and our findings in Tg models indicates that the ERC is a useful parameter to evaluate drug therapeutic potential.…”
Section: Discussionmentioning
confidence: 82%
“…The HP formation contains subfields with distinct neuronal cell types and specialized connectivity subserving learning and memory, visuospatial functions and other cognitive modalities [6,7]. Findings indicate that subtle pathological changes within the HP may precede global HP atrophy [8,9,10,11], and these substructures may be sequentially affected according to an anterior to posterior gradient of vulnerability [12]. Specifically, atrophy should first be evident in HP input structures, such as the ERC, before a regional atrophic pattern including the HP head, body and tail follows [12,13].…”
Section: Introductionmentioning
confidence: 99%